2015
DOI: 10.1002/hon.2238
|View full text |Cite
|
Sign up to set email alerts
|

The expression of RUNDC3B is associated with promoter methylation in lymphoid malignancies

Abstract: DNA methylation is an epigenetic modification that plays an important role in the regulation of gene expression. The function of RUNDC3B has yet to be determined, although its dysregulated expression has been associated with malignant potential of both breast and lung carcinoma. To elucidate the potential of using DNA methylation in RUNDC3B as a biomarker in lymphoid malignancies, the methylation status of six regions spanning the CpG island in the promoter region of RUNDC3B was determined in cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The RPIB9 ( RUNDC3B ) gene is a candidate of a biomarker in lymphoid malignancy which possibly serves as a mediator between Rap2 and the MAPK signaling cascade [ 28 ]. Studies have indicated that the RPIB9 gene is methylated in acute myelogenous leukemia (AML) and malignant B cells and that aza-dC enhances the expression of this gene [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RPIB9 ( RUNDC3B ) gene is a candidate of a biomarker in lymphoid malignancy which possibly serves as a mediator between Rap2 and the MAPK signaling cascade [ 28 ]. Studies have indicated that the RPIB9 gene is methylated in acute myelogenous leukemia (AML) and malignant B cells and that aza-dC enhances the expression of this gene [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Suggestively, the RUNDC3B gene was one of the most up-regulated genes in both cell lines—by 107-fold in C4-2B R and 174-fold in LNCaP R . The RUNDC3B gene encodes a poorly characterized protein that interacts with Rap2-binding protein 9 (RPIP9), a RAS family protein involved in the MAPK cascade pathway [ 44 ]. The RUNDC3B gene is nested in the same genetic locus as ABCB1 , with several RUNDC3B exons located in the complementary strand of the ABCB1 gene, and expression of RUNDC3B is associated with alternative regulation of the ABCB1 promoter and expression of ABCB1 mRNA isoforms [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has not been observed in acute myeloid leukemia (34). Therefore, RUNDC3B, expressed in various tissues such as brain, thymus, ovary, testis, leukocytes, liver, small intestines and prostate (35), is a biomarker for diagnosis and prognosis in lymphoid malignancies including acute lymphoblastic leukemia and lymphomas (32). The RUNDC3B may have a vital role in the pathogenesis of lymphoid malignancies even after allogeneic HSCT survival.…”
Section: Discussionmentioning
confidence: 99%